Study About Seedling Morphology of Selected Acacia Mill. (Fabaceae) Species and Its Significance in Plant Taxonomy - Vijay K. Meena; Soumana Datta (Innovations in Biological Science Vol. 5, 2024)
This study focuses on four commonly found species of Acacia that are mostly found in arid, semiarid, tropical and subtropical region of India: Acacia mangium Willd., A. auriculiformis A. Cunn. ex Benth., A. polyacantha Willd and A. farnesiana (Linn.) Willd. Acacia species have played a major role in the livelihood of local communities of arid and semi-arid areas such as, it provides timber to make furniture, food for humans, fodder for animals, fibers, gum or resin, medicine, in apiculture, energy fuel, kattha, tannins and also, give contribution in soil erosion control, nitrogen fixation, soil improvement, intercropping, boundary or barrier support and provide shade of trees to give relief from sun rays. Acacia species are commonly identified by their reproductive characteristics such as the indefinite number of stamens (more than 10) that are free or united only at the base and a calyx that is in valvate aestivation, pods, etc. In India, Acacia species are found in all climatic regions but they are found to play a major role in arid and semi-arid areas and affect the environment and communities. Twenty seeds of all Acacia species were collected from identified plants and verified seeds from different locations in Rajasthan and India. The seedling is the scarification of the seed coat. After germination, we observe seedling characters and make a dichotomous identification key to distinguish them. Mature Acacia are usually identified and distinguished from other plants by inflorescence and pod characteristics. Seedling taxonomy as a tool gives very significant knowledge about the process of establishment of stable adult traits in mature plants from the juvenile stage. This work presents as an additional tool for distinction at early stages where these reproductive characteristics are absent.